2015
DOI: 10.1515/abcsb-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Spontaneous Autogamy in the Allogamous Lepidopteran Orchid Gymnadenia Conopsea (L.) R. Br. (Orchidaceae)

Abstract: Studies of plant breeding systems are particularly important when they involve facultative processes, which can be overlooked in natural conditions. This especially applies to species that are considered allogamous, due to their pollination syndrome and floral architecture. We examined the potential level and factors enabling or limiting spontaneous autogamy in three populations of the lepidopteran orchid Gymnadenia conopsea. Using a bagging experiment, we noted the stages of the anther thecae and the position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In the case of G. conopsea, the mean seed number per capsule was the same as that in naturally developed fruits in the ZAB2 population observed in 2013 (Tałałaj and Skierczyński, 2015). A similar level of 2044 seeds was also obtained after natural pollination by Salisbury (1942) and 1675 seeds by Vakhrameeva et al (2008).…”
Section: Discussion Induced Autogamysupporting
confidence: 74%
See 2 more Smart Citations
“…In the case of G. conopsea, the mean seed number per capsule was the same as that in naturally developed fruits in the ZAB2 population observed in 2013 (Tałałaj and Skierczyński, 2015). A similar level of 2044 seeds was also obtained after natural pollination by Salisbury (1942) and 1675 seeds by Vakhrameeva et al (2008).…”
Section: Discussion Induced Autogamysupporting
confidence: 74%
“…To verify the mechanism and time of spontaneous autogamy in this species, we carried out further research in three populations from northeast Poland in 2013 (Tałałaj and Skierczyński, 2015). Using a bagging experiment, we noted the stages of the anther thecae and the positions of the pollinaria at five phenological stages of the flower.…”
Section: Spontaneous Autogamymentioning
confidence: 99%
See 1 more Smart Citation
“…For the particular pollinarium stages with the pollinia hanging free outside the thecae, massula disintegration was differentiated between the years, although the similar maximum fraction of approximately 0.30 records was achieved for each pollinarium stage P2, P3, P4 and P7. Whereas spatial and temporal differences in pollinium disintegration within the same flower may result from differences in the habitat humidity (Catling 1990;Peter and Johnson 2006;Tałałaj and Skierczyński 2015), we found that the habitat played a minor role in auto-pollination and fruit development of D. fuchsii.…”
Section: Discussionmentioning
confidence: 49%
“…Among these species, 5 species were identified as obligatorily autogamous and 2 species as facultatively autogamous, and for 10 species, this mechanism was recognized as accidental or questionable. This list continues to be augmented (Suetsugu 2013(Suetsugu , 2015Tałałaj and Skierczyński 2015). Accidents of caudicle bending within flowers (without data about self-fertilization) were noted in three species widely distributed in Europe in the genus Dactylorhiza: D. maculata, D. incarnata and D. majalis (Martens 1926;Groll 1965;Reinhard 1977;Dressler 1981).…”
Section: Introductionmentioning
confidence: 99%